Impact of consultant obstetric presence on serious incidents. Issue 3 (25th July 2019) - Shawer, Sherif; Rowbotham, Shirley; Heazell, Alexander; Kelly, Teresa; Vause, Sarah
Abstract : Purpose: Many organisations, including the Royal College of Obstetricians and Gynaecologists, have recommended increasing the number of hours of consultant obstetric presence in UK National Health Service maternity units to improve patient care. St Mary's Hospital, Manchester implemented 24-7 consultant presence in September 2014. The paper aims to discuss these issues. Design/methodology/approach: To assess the impact of 24-7 consultant presence upon women and babies, a retrospective review of all serious clinical intrapartum incidents occurring between September 2011 and September 2017 was carried out by two independent reviewers; disagreements in classification were reviewed by a senior Obstetrician. The impact of consultant presence was classified in a structure agreed a priori . Findings: A total of 72 incidents were reviewed. Consultants were directly involved in the care of 75.6 per cent of cases before 24-7 consultant presence compared to 96.8 per cent afterwards. Negative impact due to a lack of consultant presence fell from 22 per cent of the incidents before 24-7 consultant presence to 9.7 per cent after implementation. In contrast, positive impact of consultant presence increased from 14.6 to 32.3 per cent following the introduction of 24-7 consultant presence. Practical implications: Introduction of 24-7 consultant presence reduced the negative impact caused by a lack of, or delay in, consultant presence as identified by serious untoward incident (SUI) reviews. Consultant presence was more likely to have a positive influence on care delivery. Originality/value: This is the first assessment of the impact of 24-7 consultant presence on the SUIs in obstetrics.